Key technologies for 3D visualization of underground monitoring data in coal mine - Long CHEN (Meikuang Anquan)
For the three-dimensional visualization demand of monitoring data on the three-dimensional roadway model generated by any modeling software, the key technologies of three-dimensional visualization of monitoring data are proposed. By integrating the roadway centerline with the three-dimensional roadway model and using the roadway coloring technology, the dynamic effect rendering of the complete roadway or a certain roadway area is realized. According to the GPU data transmission principle, storing data as textures for transmission effectively solves the problem of unfixed data volume transmission. Combining personnel positioning data and real-time sensor data, the calculation principle of underground personnel intensity data and sensor intensity information is studied to improve the calculation method of sensor data intensity value, and a color mapping method with adaptive threshold adjustment and the color mapping technology of hot spot data is proposed. The research results are applied in Shanxi Tiandi Wangpo Coal Mine. The monitoring data is correctly displayed and the expected effect is achieved.